2022
DOI: 10.1016/j.radi.2021.09.015
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy concerns: Findings from a Ghana clinical radiography workforce survey

Abstract: Introduction: Vaccination is a key global strategy to mitigate the clinical impact of the COVID-19 virus. As part of local efforts to manage the outbreak, the government of Ghana announced its intention to vaccinate its population starting with essential and high-risk workers including radiographers. However, there were reports of hesitance to receiving the vaccine among the radiography workforce. This study was undertaken prior to the intended vaccination exercise to assess the willingness and concerns of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Fifty-eight articles reported on acceptance, with acceptance percentages of COVID-19 vaccine ranging from 15.4% 52 to 90%. 31 Among the 58 articles, nine studies reported $ 80% 26,27,31,32,36,[53][54][55][56] of their participants would accept/take the COVID-19 vaccine when available, 27 studies reported between 50% and 79%, [28][29][30][34][35][36]46,47,51,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and 15 studies reported , 50%. 36,45,49,50,52,[74][75][76][77][78][79][80]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-eight articles reported on acceptance, with acceptance percentages of COVID-19 vaccine ranging from 15.4% 52 to 90%. 31 Among the 58 articles, nine studies reported $ 80% 26,27,31,32,36,[53][54][55][56] of their participants would accept/take the COVID-19 vaccine when available, 27 studies reported between 50% and 79%, [28][29][30][34][35][36]46,47,51,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and 15 studies reported , 50%. 36,45,49,50,52,[74][75][76][77][78][79][80]…”
Section: Resultsmentioning
confidence: 99%
“…31 Among the 58 articles, nine studies reported $ 80% 26,27,31,32,36,[53][54][55][56] of their participants would accept/take the COVID-19 vaccine when available, 27 studies reported between 50% and 79%, [28][29][30][34][35][36]46,47,51,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and 15 studies reported , 50%. 36,45,49,50,52,[74][75][76][77][78][79][80][81][82] Of 58 studies, 31 reported factors that influence the desire to be vaccinated and were grouped as ...…”
Section: Resultsmentioning
confidence: 99%
“…However, not much is known about the acceptance of the COVID-19 vaccines among the general population. Existing studies in Ghana have examined the intention of the general population [32,33,51,52] and health workers [53,54] to vaccinate against COVID-19. However, these studies were conducted during the period vaccines had not been rolled out in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…To increase vaccination rates, the GHS instituted a national COVID-19 vaccination day in February 2022 and inaugurated a second campaign coinciding with Africa immunization week in March of the same year [ 17 ]. Surveys during the pandemic indicate that the hesitancy is fueled by different factors that are changing over time, such as the fear of side effects and the lack of trust in the vaccines [ 18 , 19 ]. Similar to many other countries, Ghana has witnessed the widespread transmission of misinformation during the pandemic on the web and offline, including the period during promotion of COVID-19 vaccines [ 20 ].…”
Section: Introductionmentioning
confidence: 99%